Comparative study of robotic-assisted single-incision-plus-one port and single-incision laparoscopic choledochal cyst excision - Zhang, Ling; Chen, Shan; Lin, Yang; Wang, Jianbin; Qiu, Xinyi; Li, Lizhi (Frontiers in Pediatrics, 2024)
Objective To compare the efficacy of robotic-assisted single-incision-plus-one-port laparoscopic choledochal cyst excision (R-SILC + 1) and single-incision laparoscopic choledochal cyst (SILC) in treating pediatric choledochal cyst (CDC). Methods We retrospectively analyzed the clinical data of patients diagnosed with CDC in our hospital from June 2021 to October 2023. Among them, patients underwent either R-SILC + 1 or SILC procedures. Demographic parameters, operative details, and postoperative outcomes were studied. Results A total of forty-nine patients were included, with 23 children undergoing R-SILC + 1 and 26 children undergoing SILC. There were no statistically significant differences in demographic data, postoperative pain scores, and postoperative complication rates between the two groups (all p > 0.05). Compared with the SILC group, the R-SILC + 1 group demonstrated less intraoperative bleeding volume (10.4 ± 3.6 vs. 15.0 ± 3.6 ml, p < 0.05), a shorter indwelling time of the abdominal drainage tube [5(5,6) vs. 7(5.8,8.3) d, p < 0.05], a shorter postoperative fasting time [4(3,4) vs. 6(5,7) d, p < 0.05], and a shorter postoperative discharge time [6(6,7) vs. 8(6,11) d, p < 0.05]. However, the R-SILC + 1 group had a longer operation time [388(295,415) vs. 341(255.8,375.2) min, p < 0.05] and higher hospitalization cost (7.9 ± 0.4 vs. 3.2 ± 0.3 ten thousand, p < 0.05). Conclusion Compared with the SILC group, the R-SILC + 1 group demonstrated clear advantages in treating pediatric CDC, but it is associated with a prolonged learning curve and operation time, and high costs. With improvements in physician experience and technological advancements, its potential will be further unleashed.